Maribor in vojaška infrastruktura od sredine 19. stoletja do konca prve svetovne vojne - Kladnik, Tomaž (Annales. Series historia et sociologia, 2019)
Based on the study of archival sources and scholarly literature, the paper discusses the urban development of the city of Maribor, specifically the construction and development of military infrastructure and its impact on the development of the city and the economic and daily life on the Slovenian territory until the end of the First World War. With the construction of the Southern Railway and its arrival in the city in 1846, Maribor, with its location as the centre of modern imperial transport routes, gained an important military-strategic role, with exceptional economic and transport development opportunities. It soon had the largest military infrastructure in this part of Austria-Hungary. The First World War placed Maribor at the heart of military and political developments, as the city became the headquarters of the Southwestern Front Command.
Keywords: Austria- Hungary; Austria-Ungheria; Avstro-Ogrska; economic development; gospodarski razvoj; infrastruttura militae; Maribor; military infrastructure; military life; Slovenian territory; slovensko ozemlje; sviluppo economico; territorio sloveno; vita militare; vojaška infrastruktura; vojaško življenje